2020
DOI: 10.1177/2320206820975971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marginal Adaptation of Different Resin-Ceramic CAD/CAM Crowns: An In Vitro Study

Abstract: Aim: To compare the marginal adaptation of crowns fabricated by using three different resin-ceramic computer-aided design/computer-aided manufacturing (CAD/CAM) materials. Materials and Methods: Crowns fabricated from three different resin-ceramic CAD/CAM blocks, applied on a typodont premolar (#14), were tested with regard to marginal adaptation, in this in vitro study. The typodont maxillary first premolar was prepared to serve as the master die and digitized with an intraoral scanner. The same virtual crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Conversely, a study by Azarbal et al [10], in 2017, reported that VE crowns fabricated using the CEREC milling system showed marginal adaptation superior to that of lithium disilicate crowns [10]. In this study, all the hybrid material crowns produced MG values within the clinically acceptable range [9] similar to previous studies [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, a study by Azarbal et al [10], in 2017, reported that VE crowns fabricated using the CEREC milling system showed marginal adaptation superior to that of lithium disilicate crowns [10]. In this study, all the hybrid material crowns produced MG values within the clinically acceptable range [9] similar to previous studies [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the accuracy of cast coping obtained through Cast-LWT depends on the accuracy of wax pattern and technical accuracy, i.e., wax composition, tank and block temperature, time specified for cooling of the wax pattern, and the firing temperature necessary to achieve desirable outcomes [30]. In addition, distortion of inlay casting wax, its shrinkage, and high investment expansion affects the precision of copings fabricated with Cast-LWT [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the low hardness values of resin-ceramic materials are found to prevent the wear of opposing dentition and enable rapid milling and to minimize marginal chipping which is associated with better marginal adaptation. (18) The mechanical properties of the resin-ceramic CAD-CAM block materials tested were within the acceptable range for fabrication of single restorations according to the ISO standard for ceramics (ISO 6872:2008). Cerasmart was observed to have superior flexural strength and better internal fit (19) ; for these reasons, the endocrown was fabricated by resin nanoceramic block (GC ® Cerasmart, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 90%